2022
DOI: 10.1021/acs.jpcb.2c00928
|View full text |Cite
|
Sign up to set email alerts
|

Ratiometric Fluorescence Detection of Mg2+ Based on Regulating Crown-Ether Modified Annihilators for Triplet–Triplet Annihilation Upconversion

Abstract: Detection of magnesium ion has been of great significance considering its critical physiological activities. Herein, we report ratiometric fluorescence detection of Mg2+ with high sensitivity and selectivity based on triplet–triplet annihilation (TTA) upconversion for the first time. Crown-ether functionalized anthracene derivatives were synthesized, which bifunctionally acted as not only annihilators to construct TTA upconversion systems but also the recognition probes for Mg2+ based on the photoinduced elect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 42 publications
1
3
0
Order By: Relevance
“…The relationship of I / I 0 and [Mg 2+ ] presented better linearity ( R 2 = 0.9941) in CH 3 CN before reaching its saturation state. The detection concentration of Mg 2+ under excitation of 371 nm reached 10 –5 M, comparable to that of a 4′-(9-anthraceneacetamido)­benzo-15-crown-5 ether/PtOEP system reported in the literature …”
supporting
confidence: 76%
See 1 more Smart Citation
“…The relationship of I / I 0 and [Mg 2+ ] presented better linearity ( R 2 = 0.9941) in CH 3 CN before reaching its saturation state. The detection concentration of Mg 2+ under excitation of 371 nm reached 10 –5 M, comparable to that of a 4′-(9-anthraceneacetamido)­benzo-15-crown-5 ether/PtOEP system reported in the literature …”
supporting
confidence: 76%
“…Upon a comparison of the structures of rectangles Pt1 and Pt2, it was found that the presence of benzyl −CH 2 − subunits of Pt2 made the size and binding property of the polyether ring obviously vary from that of Pt1. The 40 In conclusion, a class of novel molecular rectangles functionalized with crown ethers have been readily assembled using a phenanthro crown ether, biphenyl polyether-bridged bicarboxylate ligands, and a Pt-based binuclear molecular clap. We demonstrated that this new macrocyclic class of cation receptors can selectively bind and detect Na + and Mg 2+ cations via an emission spectral technique.…”
mentioning
confidence: 99%
“…Tian et al 28 proved that benzo[ b ]quinolizinium-benzo-15-crown-15 is selective with respect to NH 4 + , Li + , Na + , K + , and Ba 2+ . Ye and co-workers 29 investigated benzo-15-crown-5-anthracene-derivatives and showed its high sensitivity and selectivity with respect to NH 4 + , Li + , Na + , K + , Zn 2+ , Pb 2+ , Mn 2+ , Cd 2+ , and Ca 2+ . Marraccini et al 30 analyzed diaza-18-crown-6-hydroquinoline derivatives, whereas Zahedi and Ghasemi 31 studied 18-crown-6 for extracting magnesium from seawater, but were not satisfied with its selectivity.…”
Section: Introductionmentioning
confidence: 99%
“…Mg 2+ is the most abundant intracellular divalent cation and plays a significant physiological role in numerous cellular processes [16]. Moreover, excessive Mg 2+ ingestion may lead to pathological lesions in the cardiovascular, nervous, urinary, and hematopoietic systems [17,18]. However, most methods for detecting Mg 2+ still need expensive instrumentations, such as atomic absorption spectroscopy (AAS) and inductively coupled plasma-mass spectrometry (ICP-MS), and complex organic fluorescent probes [18][19][20].…”
Section: Introductionmentioning
confidence: 99%